Innate immune responses to RNA: sensing and signaling - Luan, Xiaohan; Wang, Lei; Song, Guangji; Zhou, Wen (Frontiers in Immunology, 2024)
Nucleic acids are among the most essential PAMPs (pathogen-associated molecular patterns). Animals have evolved numerous sensors to recognize nucleic acids and trigger immune signaling against pathogen replication, cellular stress and cancer. Many sensor proteins (e.g., cGAS, AIM2, and TLR9) recognize the molecular signature of infection or stress and are responsible for the innate immune response to DNA. Remarkably, recent evidence demonstrates that cGAS-like receptors acquire the ability to sense RNA in some forms of life. Compared with the nucleic-acid sensing by cGAS, innate immune responses to RNA are based on various RNA sensors, including RIG-I, MDA5, ADAR1, TLR3/7/8, OAS1, PKR, NLRP1/6, and ZBP1, via a broad-spectrum signaling axis. Importantly, new advances have brought to light the potential clinical application of targeting these signaling pathways. Here, we highlight the latest discoveries in the field. We also summarize the activation and regulatory mechanisms of RNA-sensing signaling. In addition, we discuss how RNA sensing is tightly controlled in cells and why the disruption of immune homeostasis is linked to disease.